LOCAL FINANCE AS AN OBJECT OF PUBLIC ADMINISTRATION: THE ESSENTIAL CHARACTERISTICS AND PLACE IN THE FINANCIAL SYSTEM OF THE STATE - Goncharenko , M. V. (Theory and Practice of Public Administration, 2021)
The article is devoted to clarifying the essence of local finance as an object of public administration and their role in the financial system of the state in the context of decentralization. The content, main features and approaches to the structuring of the financial system of the state are generalized, the role of local finances in the financial system and the system of public finances is determined. It is proved that local finances are not a component of state finances, although they are significantly dependent on them, but are an independent component of public finances. The material basis of local finances are local government budgets, including special budget funds for special purposes; extra-budgetary funds of local governments; cash funds of utility banks; funds of communal (municipal) enterprises, institutions and organizations. The peculiarities of local government finances as a component of the public finance system are systematized. It is determined that local finances realize their economic essence through functions, including distribution and redistribution of GDP, formation of fiscal policy at the local level, financing of public services, ensuring economic growth of territories. Theoretically, local finance is a system whose structural components are revenues, expenditures, entities, objects that are interconnected by economic relations, as well as a set of major financial institutions, among which the main role in ensuring the performance of functions and tasks local authorities play the local budget. Scientific views on the interpretation of the concepts of “local finance” and “local government finance” are studied. The direction of further research is the harmonization of terminology and scientific substantiation of the holistic concept of local financial management in the new administrative-territorial system and the continuation of decentralization reform.